The Influence of Employee Competence on the Effectiveness of Motor Vehicle Tax Management at the Regional Revenue Management Center in Tasikmalaya Regency - Ira Nuraidah; Arifah Rosmayudi; Dian Herlina; Nidia Rismania Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Taxes are a key source of revenue for both national and local governments, serving an important function in supporting development and enhancing public welfare. Motor vehicle tax is one of the potential contributors to local revenue; however, taxpayer compliance in Tasikmalaya Regency remains low, as reflected in the high number of vehicles that have not renewed their registration and the limited use of digital payment services. This situation may hinder the region’s revenue performance. Therefore, this study examines the influence of employee competence on the effectiveness of motor vehicle tax management at the Tasikmalaya Regency Regional Revenue Management Center. Using a quantitative approach with two variables—employee competence (X) and management effectiveness (Y)—the study applies simple linear regression analysis. The findings show that employee competence significantly affects tax management effectiveness, contributing 86.6% with a regression coefficient of 1,094. The hypothesis testing yields a t-value of 10.486 and a significance level of 0.000, which is below the 0.005 threshold. These results highlight the essential role of employee competence in improving motor vehicle tax management. In conclusion, employee competence is identified as a key factor in enhancing the effectiveness of motor vehicle tax management in Tasikmalaya Regency.